THE ROLE OF EDUCATORS IN ADDRESSING THE USE OF ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION: A NARRATIVE REVIEW - Mosae, Tlalane; Kaushal, Rekha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Integrating artificial intelligence (AI) in higher education offers great opportunities but comes with challenges. This study highlights educators' key role in addressing AI in higher education, focusing on four main areas: curriculum development, ethical issues, teaching methods, and challenges in AI integration. It reviews current research to show how educators can teach AI effectively, raise ethical awareness, and adjust teaching strategies to use AI tools well. The results underscore the need for ongoing training for educators, AI literacy, and interdisciplinary collaboration to help educators prepare students for an AI-driven future. The review also offers practical recommendations to ensure AI enhances teaching while keeping it focused on human connections. Moreover, balancing innovation with ethical responsibility is essential to ensure that AI is a tool for empowerment rather than a source of inequity.